Between the expected and the experienced: assessing the public’s perception of journalism ethics and objectivity in Latvia - Rožukalne, Anda; Strode, Ieva (Frontiers in Communication, 2025)
IntroductionOur study refers to the calls of various scholars to add the media users’ view and the audience’s agency role to the evaluation of media and journalism. The objective of this study is to explore the audience’s perception of media and journalistic ethics in times of various global and geopolitical crises.MethodsWe use a quantitative survey (N = 1,019, 2022) and two focus group studies (14 groups, N = 80, 2022, 2023) to describe the Latvian audiences’ assessment of professional journalism ethics principles and their implementation.ResultsThe Latvian public is critical of the ethical practice of journalists, with almost half of the respondents observing various violations of professional ethics and recognizing different journalistic cultures according to their degree of responsibility.DiscussionEvaluating data according to the journalistic ethical orientation model, it is found that representatives of the Latvian media audience support absolutist and exceptionist approaches, as they place high demands on journalists, putting the principle of objectivity and the duty of journalists to ensure the diversity of opinions in the foreground.